Uma aplicação de análise de decisão com o método AHP Processo de hierarquia analítica: um estudo sobre adoção de Sistema eletrônico de cobrança no Transporte público urbano - Sena, Lunardo Alves de (2007)
This thesis carries through an application of Analysis of Multicriterion Decision with use of the method of Analytical Hierarchy Process (AHP) in the problematic one of taking of decision of the adoption of electronic collecting in the system of urban transport in the country, a subject that has been controversial. A modeling of criteria and alternatives is carried through and applied a questionnaire based on method AHP the excellent actors in the system of urban transport - Leading of the Managing Agency Public Municipal theatre of Urban Transports, Controller of Company of Bus, Controller of Labor union, Controller of Union of Companies, Communitarian Leader. The considered alternatives were: the maintenance of the current state with collectors, the implementation of electronic collection without collectors, and the implementation of electronic collection with collectors. The used criteria were: job, impact in the fare, control of the system, easiness of use, information. The study was carried through in the city of Natal, RN, where if the adoption of electronic collection argues and where this implementation in some bus lines between Natal and Parnamirim exists, city that integrates the region of the great Natal. The main results of the method evidence in a dimension, the viability of use of method AHP with questionnaire by means of validation of the judgments with analysis of variance beyond proper the normal mechanisms of analysis of consistency to the method, and in another one, the contribution of the analysis boarding multicriterion to become the judgments more clearly. The main results of the analysis help to show that although to models of criteria and distinct judgments of the actors, the method evidenced that it has inclination the adoption of the electronic collection on the current situation, even so with divergences between the maintenance or not of the collector. The research points to the possibility of accomplishment of the application of the AHP in successive rounds of judgments